The role of automation of the customs tax system in increasing the percentage of tax revenues in financing the general budget out of the gross domestic product: "A comparative analytical study of selected developing countries, with special reference to iraq for the period between 1997-2021" - Azab, Sami; Yassin Al Safar, Ahmed (Humanities Journal of University of Zakho, 2024)
The present study aims to describe and analyze the role of automation in increasing the proportion of tax revenues in the general budget of the gross domestic product of selected countries that have gone through the experience of introducing automation into the tax system and converting it from a traditional tax system to a modern system based on technical devices, by observing the change in the percentage of these revenues and their averages before Applying automation and after it, increasing tax revenue, complying with its payers, and reducing the process of tax evasion. The proportion of tax revenues in the general budget of countries was compared to the gross domestic product of these countries before and after the application of automation. These data were taken from the International Monetary Fund and central banks in developing countries, from 1997 to 2021. This period was divided into five equal periods, and the average rate of tax revenue was compared among these periods by analyzing these data and extracting the arithmetic averages before and after the application of automation to find out the change that occurred after the introduction of automation in the tax system as well as measuring the research variables and their outputs by using Eviews (12) program . The results arrived at in the present study showed that there is an increase in the percentage of tax revenues in the general budget of the countries of their gross domestic product, which went through the experience of introducing automation in their tax system after the application of automation by noting an increase in its percentage in the general budget of the countries under study . The study also found that there is a statistically significant relationship between the tax revenues in the countries general budget from the gross domestic product and perecentage of customs tax revenues from the total tax revenues . The study recommended that the Iraqi tax system needs to be fixed and restructured in different ways, inculding the adminstrative and legal aspects and the eradication of financial and adminstrative corruption in the different tax institutions, especially at border crossings as customs taxes increase and support the the country revenue taxes, and in turn support the country general budget. The sudy also suggested to condcut more future studies on this subject.